Risk factors modulating the course of low-grade squamous intraepithelial lesions in women of reproductive age - T. S. Prisyazhnaya; V. A. Mikhaylyukova; I. V. Berlev; A. V. Malek (ABV-press, 2021)
Background. Infection with oncogenic types of human papillomavirus (HPV) is the leading cause of cervical cancer and its immediate precursors - squamous intraepithelial lesions. However, the persistence of HPV may not be sufficient for the occurrence of malignant transformation, and there may be other exogenous or endogenous factors that, in combination with the virus, increase the risk of developing and progressing cervical neoplasia.Objective: identification of risk factors that modulate the course of low-grade squamous intraepithelial lesions (LSIL) in women of reproductive age.Materials and methods. In 110 women aged 18 to 45 years with a diagnosis of LSIL, we evaluated the impact of risk factors (sexual behavior, reproductive function, contraceptive methods, smoking, HPV infection) on the course of the process (recovery, persistence or progression) during the 12-month follow-up period. HPV testing was performed by real-time PCR.Results. The average age of the study participants was 31.55 ± 7.17 years. Our observations showed that frequent artificial abortions, the practice of risky sexual behavior (early sexual debut, frequent change of sexual partners) increased the risk of persistence and progression of mild cervical cytological abnormalities. The use of oral contraceptives, barrier contraception and smoking did not affect the outcome of the disease.The prevalence of HPV among women with LSIL was 70.91 % (78/110). The predominant types were HPV 16 (35.45 %), HPV 33 (12.73 %) and HPV 18 (12.73 %). HPV 16 was more common in the progression group (62.50 %) than in the regression and persistence groups (14.63 % and 43.40 %, p <0.05). Progression of neoplasias was more often observed in patients with signs of multiinfection of the cervical epithelium with HPV. Single HPV infection was higher in the group of recovered women.Conclusions. The study found that a large number of induced abortions, the practice of risky sexual behavior, the presence of HPV type 16 and multiple HPV infection are factors contributing to the persistence of LSIL and progression to HSIL. These data may be useful for the management of women with mild cervical cytological abnormalities.